2013
DOI: 10.1161/strokeaha.113.677070
|View full text |Cite
|
Sign up to set email alerts
|

Onset Headache Predicts Good Outcome in Patients With First-Ever Ischemic Stroke

Abstract: Background and Purpose-The study aimed to assess whether onset headache is an ominous sign in patients with first-ever ischemic stroke. Methods-A large population of ischemic stroke patients was obtained from the Taiwan Stroke Registry. Stroke subtypes were classified by the Trial of ORG 10172 in Acute Stroke Treatment (TOAST) criteria. On the basis of the International Classification of Headache Disorders, second version, onset headache was defined as a new headache that developed at the onset of ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 31 publications
5
62
1
Order By: Relevance
“…18 We did not observe such differences between the 2 groups. The clinical implication of headache at onset in patients with AIS is controversial and reported data are limited by small sample sizes.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…18 We did not observe such differences between the 2 groups. The clinical implication of headache at onset in patients with AIS is controversial and reported data are limited by small sample sizes.…”
Section: Discussioncontrasting
confidence: 51%
“…18 Although the difference was not significant, our headache population showed potential toward a better outcome compared to the nonheadache cohort. This tendency was observed in univariate analysis only and may be attributed to the difference in age between the 2 groups.…”
Section: Discussionmentioning
confidence: 68%
“…2 For this purpose, the authors defined anatomic localizations within the posterior circulation such as the cortex supplied by the posterior cerebral artery, thalamus, midbrain, pons, medulla, and cerebellum. 1 In this study, patients with onset headache were more likely to have ischemia in the posterior circulation, especially patients with cerebellar infarction. The conclusion was that onset headache was associated with modest but significantly better outcomes after ischemic stroke.…”
Section: To the Editormentioning
confidence: 64%
“…We read with interest the article by Chen et al 1 reporting that onset headache predicts better outcome in patients with first-ever ischemic strokes. The study was performed in a large cohort and showed interesting results.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation